the UJI EFEKTIVITAS TABLET EKSTRAK DAUN BINAHONG (Anredera cordifolia (Ten.) Steenis) TERHADAP PENURUNAN KADAR KOLESTEROL TOTAL PADA HEWAN MENCIT JANTAN PUTIH (Mus : UJI EFEKTIVITAS TABLET EKSTRAK DAUN BINAHONG (Anredera cordifolia (Ten.) Steenis) TERHADAP PENURUNAN KADAR KOLESTEROL TOTAL PADA HEWAN MENCIT JANTAN PUTIH (Mus - lestari, gina (Oceana Biomedicina Journal, 2024)
Introduction : Binahong leaf (Anredera cordifolia (Ten.) Steenis) is a plant which is actually a wild plant. Sungkai leaves contain flavonoids, alkaloids, tannins, triterpenoids, saponins. This study aims to determine the effectiveness of Binahong leaf ethanol extract tablets (Anredera cordifolia (Ten.) Steenis) on blood cholesterol levels in male mice (Mus musculus). Methodes: This research is an experimental research using the Easy Touch Glucose Cholesterol Uric Acid (GCU) checking method. Thirty male white mice were divided into 6 treatment groups, namely the Normal control group, Positive control, Negative control, F1 group, F2 group, and F3 group. Where mice were measured for blood cholesterol levels on day 1 as normal cholesterol, then their cholesterol levels were raised by feeding high cholesterol quail egg yolks for 7 days then checking the blood cholesterol of mice, after that it was lowered by being treated with Binahong Leaf Extract Tablets for 7 days then checked again mice blood cholesterol. Results: The research results were analyzed using one-way ANOVA (p> 0.05) which was then tested by the Duncan showing that Binahong Leaf Extract Tablets at F3 doses of 14 mg with a reduction percentage of 20.64% had effectiveness in reducing blood cholesterol levels in male mice (Mus Musculus). Conclusion : Binahong Leaf Extract Tablets have a buffer effect on reducing total cholesterol levels in mice